The contribution of Cardinal Friedrich Egon of Fürstenberg to the building up of the picture collection of the Olomouc archbishops = Podíl kardinála Bedřicha Egona z Fürstenbergu na budováni obrazové sbírky olomouckých arcibiskupů - Zapletalová, Jana 1981-; Šima, Petr (2023)
Abstrakt(y) The text brings new findings regarding the collecting activity of Olomouc Archbishop Cardinal Friedrich Egon of Fürstenberg (1813-1892), whose acquisition activity in works of art has so far been in the shadow of his construction activities and has been unfairly undervalued. The article makes available the results of archival research. It is based, on the one hand, on the study of accounting documents, especially from Cardinal Fürstenberg's longer stays in Rome, which have so far only been studied on a selective basis. It also makes available information unknown until recently, contained in the income and expenditure books of the Archbishop's Secretariat from 1854-1873. The study of accounting documents has made it possible to enrich the list of Fürstenberg's acquisitions for the picture collection of Olomouc bishops and archbishops with several new items and attributions. In particular, however, it has shed new light on the archbishop's acquisitions of works of art from his period in Rome. Cardinal Fürstenberg made purchases at select Roman antiquarians and maintained close contacts with the priest and senior Vatican official Marcello Massarenti Ordelaffi (1817-1905). In his time, this man, who mediated certain art purchases for the Archbishop of Olomouc, was one of the well-known collectors of the second half of the 19th century in Rome. Massarenti's collection became the basis of the collection of American tycoon Henry Walters (1812-1894) in Baltimore.
Keywords: Walters, Henry -- 1848-1931; Friedrich Egon -- Olmütz, Erzbischof -- 1813-1892; Sammlung; Kunst